Effect of Masked, White-Coat, and Sustained Hypertension on Coronary Flow Reserve and Peripheral Endothelial Functions. (May 2013) - Caliskan, Mustafa; Ciftci, Ozgur; Gullu, Hakan; Caliskan, Zuhal; Güven, Aytekin; Erdogan, Dogan; Muderrisoglu, Haldun
<x xml:space="preserve">Abstract</x> In this study, we have measured coronary flow reserve (CFR) using transthoracic echocardiography and brachial artery flow-mediated dilatation using vascular ultrasound in 36 subjects with masked hypertension (MH), 62 patients with sustained hypertension (SH), 40 patients with white-coat hypertension (WCH), and 39 healthy volunteers. CFR was significantly lower in the MH and SH groups (2.30 ± 0.39 and 2.28 ± 0.52, respectively) than in the control and WCH groups (2.85 ± 0.39 and 2.77 ± 0.41, respectively; P < .05). CFR was significantly impaired in patients with MH and SH compared with WCH and normotensive subjects. MH and SH groups are comparable with regard to cardiovascular risks and target organ damage.